Biodiversity and Climate-Smart Agriculture: A Review of Conservation and Environmental Aspects of PUSAKA BUMI Program - Fadhila, Mezy; Fajar, Riezqi; Pujiarso, Fajar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Mangoes are a widely cultivated commodity, integral to the identity and economy of Indramayu Regency. However, mango cultivation faces significant challenges, primarily due to climate change and soil degradation. These two factors negatively affect the quantity and quality of mango production, threatening the sustainability of local agriculture and farmers’ livelihoods. In response, Pertamina Patra Niaga Integrated Terminal Balongan, in collaboration with the Salam Tani Farmer Group in Sliyeg Lor Village, initiated the Biodiversity Cultivation Sanctuary Center (Pusat Suaka Budidaya Keanekaragaman Hayati/PUSAKA BUMI) program as an effort to conserve the local Indramayu mango (Mangifera indica) varieties. Using a qualitative descriptive approach, this paper aims to explain the biodiversity conservation efforts, particularly for local mango varieties in Indramayu Regency, through the PUSAKA BUMI Program and its environmental impacts. The results show that the local mango conservation efforts are manifested in two ways. First, the implementation of Climate-Smart Agriculture (CSA) involves developing a botanical garden equipped with a greenhouse and smart farming systems to create environmental adaptations to climate change. Second, the Bio-Retra innovation utilizes agricultural biomass residues to produce biochar and liquid organic fertilizer as a replacement for chemical fertilizers to restore soil health.